FORMING AN INTEGRATED INVESTIGATION METHOD FOR CRIMINAL TRANSACTIONS IN PRECIOUS METALS AND PRECIOUS STONES - Nikonovich, Sergey (Revista Inclusiones, 2020)
The Russian Federation ranks high in top 10 countries producing precious metals and precious stones. Since January 2010, Russia has been the leader of the global diamond mining industry. The Russian diamond complex makes marketable products for more than $2.3 billion each year. The regions that are the richest in precious metals and precious stones are located in the Russian Far East. For example, the Republic of Sakha (Yakutia) mines about 30% of all gold and 99.7% of all diamonds produced in the country annually. The gold produced in Magadan Oblast accounts for 30% of the total amount. Amur Oblast mines 12-13 tons of gold on an annual basis. In addition to gold, Khabarovsk Krai and Krasnoyarsk Krai produce silver, platinum and other platinum group metals. The Urals are rich in diamonds (0.3% of diamonds are mined in Perm Oblast), emeralds and chrysoberyl (alexandrite), whose reserves consist of 11.5 million tons. Arkhangelsk Oblast holds 18.7% of the country's diamond reserves and started their industrial mining in 2015. In 2011, the scope of precious metals production reached the pre-reform level for the first time. Today Russia exports 75% of its gold and diamonds. The country has also the most explored reserves of precious minerals. Currently, its central regions conduct an economic assessment of newly discovered deposits of precious minerals.